Membangun Generasi Anti-Korupsi Terhadap Peran dan Tantangan Edukasi Antikorupsi pada Gen Z di Era Digital - Kaela Isadora; Raifan Wahyu Satria; Rifna Angraini; Siti Nur Hikmah; Rahayu Lestari (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2025)
Since they were raised in the internet age, Generation Z will play a crucial part in future initiatives to end corruption. In addition to outlining the difficulties encountered in its implementation, this study attempts to investigate how anti-corruption education shapes the anti-corruption character of this generation. In addition to formal education, Gen Z-friendly digital channels like social media and technology-based learning apps can also be used to deliver anti-corruption education. The primary barriers, however, include issues like low computer literacy, a lack of understanding of the consequences of corruption, and the role that a permissive social context plays in corruption.Through the use of a qualitative methodology, this study discovered that education founded on integrity values, cross-sector collaboration, and innovative technology use can be a successful strategy for producing a generation that is cognizant of and sensitive to the risks associated with corruption. These results are expected to aid in the creation of more inclusive and contemporary anti-corruption education initiatives in the digital age.